1992
DOI: 10.1007/bf03187137
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of sexual harassment as a function of sex of rater and incident form and consequence

Abstract: The purpose of this study was to investigate differences in perceptions of two "severity dichotomies" present in the Equal Employment Opportunity Commission Guidelines on sexual harassment. Alale and female undergraduates (N = 198), from a predominately white midwestern university, were given one of four statements based on these guidelines, varying "form" (physical/verbal) and "consequence" (economic injury/hostile environment) of the behavior. Analysis of variance results showed females rated the incident as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…In recent years, social scientists, policy makers, and the general public have given an extensive degree of attention to issues associated with sexual harassment. As a result, there has been an increasing number of empirical investigations which focused on those factors which affect perceptions of such harassment (Bursik, 1992;Gervasio & Ruckdeschel, 1992;Popovich, Gehlauf, Jolton, Somers, & Godinho, 1992). One of the major areas of focus in sexual harassment research has been the effect of subject gender.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, social scientists, policy makers, and the general public have given an extensive degree of attention to issues associated with sexual harassment. As a result, there has been an increasing number of empirical investigations which focused on those factors which affect perceptions of such harassment (Bursik, 1992;Gervasio & Ruckdeschel, 1992;Popovich, Gehlauf, Jolton, Somers, & Godinho, 1992). One of the major areas of focus in sexual harassment research has been the effect of subject gender.…”
mentioning
confidence: 99%
“…One of the major areas of focus in sexual harassment research has been the effect of subject gender. Interestingly enough, researchers have demonstrated that perceptions vary as a function of gender; that is, females tend to be more sympathetic to the target than do males (Gutek, 1985;Jones & Remland, 1992;Popovich et al, 1992;Summers, 1991), do not vary as a function of gender (Baker, Terpstra, & Cutler, 1990;Bursik, 1992;Jones, Remland, & Brunner, 1987), or vary on some issues and not others (Castellow, Wuensch, & Moore, 1990;Jones et al, 1987). Most recently, Frazier, Cochran, and Olson (1995) have contended that research on gender differences in sexual harassment perceptions "needs to move beyond documenting differences to identifying both mediators and moderators of such differences" (p. 34).…”
mentioning
confidence: 99%
“…Previous researchers have demonstrated that sexual harassment perceptions vary as a function of gender (Gutek, 1985;Jones & Remland, 1992;Popovich, Gehlauf, Jolton, & Somer, 1992;Summers, 1991), do not vary as a function of gender (Baker, Terpstra, & Cutler, 1990;Bursik, 1992;Jones, Remland, & Brunner, 1987), or vary on some issues but not others (Castellow, Wuensh, & Moore, 1990;Jones et al, 1987). Consequently, no specific predictions were made for participant gender.…”
Section: Gender Effectsmentioning
confidence: 93%
“…What may be seen by one person as innocent courting behavior, which happens to occur in the workplace, may be seen by another person as offensive and intimidating behavior which hinders his or her ability to effectively perform the job. For example, a number of studies have noted that females tend to rate sexually oriented behavior as sexual harassment to a greater degree than do their male counterparts (e.g., Gutek, Morasch, & Cohen, 1983;Gutek, Nakamura, Gahart, Handschumacher, & Russell, 1980;Konrad & Gutek, 1986;Popovich, Gehlauf, Jolton, Somers, & Godinho, 1992;Popovich, Licata, Nokovich, Martelli, & Zoloty, 1986;Powell, 1983Powell, , 1986Terpstra & Baker, 1986).…”
mentioning
confidence: 99%
“…Clearly, agreement among the contact persons about what constitutes sexual harassment would be required for the effective incorporation of this component into the training package. Given the lack of consensus among individuals as to what constitutes sexual harassment (e.g., Gutek et al, 1980Gutek et al, , 1983Konrad & Gutek, 1986;Popovich et al, 1986Popovich et al, ,1992Powell, 1983Powell, , 1986; Terpstra & Baker, 1986), considerable attention would need to be devoted to this component of the training package.…”
mentioning
confidence: 99%